Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3109/0284186x.2012.692884
|View full text |Cite
|
Sign up to set email alerts
|

Persistent pain, sensory disturbances and functional impairment after adjuvant chemotherapy for breast cancer: Cyclophosphamide, epirubicin and fluorouracil compared with docetaxel + epirubicin and cyclophosphamide

Abstract: Docetaxcel as adjuvant treatment for breast cancer does not increase the risk of PPBCT, sensory disturbances in the surgical area or functional impairment, but increase risk for peripheral sensory disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 21 publications
3
44
0
Order By: Relevance
“…Our results agree well with those of Osmani et al [7] reporting that 29/56 patients (52%) suffered from PN 1-13 years after treatment with docetaxel and Andersen et al reporting PN from 23% in the hands to 32% in the feet at a median of 34 months following adjuvant docetaxel [6]. This study reported only whether PN was present but not the severity of symptoms.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Our results agree well with those of Osmani et al [7] reporting that 29/56 patients (52%) suffered from PN 1-13 years after treatment with docetaxel and Andersen et al reporting PN from 23% in the hands to 32% in the feet at a median of 34 months following adjuvant docetaxel [6]. This study reported only whether PN was present but not the severity of symptoms.…”
Section: Discussionsupporting
confidence: 95%
“…This is in agreement with two other studies also demonstrating that persistent PN was associated with age older than 50-60 years [6,16] and that grade of PN during treatment was associated with a higher risk of persistent PN [16]. The latter finding underlines the importance of delaying or reducing dose in patients with grade 2, 3 and 4 PN during treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…36,39,43,50,53,55,56 However, the results from these studies were consistent with the results from studies amenable to pooling. We used the IASP criteria for the definition of persistent pain in this review; however, 14 of the included studies did not report whether their assessment of persistent postsurgical pain excluded other causes of pain; 26,[33][34][35][36]43,45,47,48,50,51,54,56,58 as such, they may have overestimated the prevalence of persistent pain.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…148 Despite the logical assumption that the use of adjuvant chemotherapy or radiotherapy would potentiate the development of PPSP, multiple studies have failed to definitively show an association. 134,149 Nevertheless, some chemotherapy is associated with an increased risk of peripheral neuropathy 150 and work in animal models of PPSP have demonstrated a role for the TRPV1 channel (whose expression is increased in CIPN) in the development of cutaneous hypersensitivity following surgery. 151 …”
Section: Risk Factorsmentioning
confidence: 99%